Bridge to Success:English for International Studies Students (Year 1) Шлях до успіху: Англійська мова для студентів міжнародних студій (Частина 1) Підручник - Bohatyrets, Valentyna; Kudelko, Zoya (Чернівецький національний університет, 2021)
For anyone who is an English Second Language (ESL) student, the most challenging aspects of the language are idioms, slang and vernacular. It can be very difficult to follow what people are saying and to make sense of it all. ESL instructors are right beside you to help but they cannot always be present to explain things. We have created an excellent study guide just for the idioms and vocabulary that an ESL student cannot live without, whether for use in the classroom or as a personal aid for anyone whose foreign language is English, “Bridge to Success: English for International Studies Students” is sure to be a welcome help. With hundreds of vocabulary words and idioms to work with, learners will find that their understanding of English has improved upon completing their study guidelines. Using a storyline to show the words in context, authors allow learners to experience what is being talked about rather than just read about it. Each chapter includes a story scene, a list of definitions, exercises including matching terms, fill in the blanks, crossword puzzles, and more, comprehension questions to think about and answer discussion questions to work on with a partner and a section to put your new knowledge to the test. After each Unit, the students are given several sample tests to practice as a springboard for their further success in taking the entrance exam for the master’s degree program. After the six chapters, the authors give an extensive list of website resources that relate to each chapter, and finally, a glossary that lists each of the hundreds of words and idioms in the book. It will make learning English a bit more fun and “hands-on”. In the course of studies, the manual will facilitate students’ acquiring the necessary language skills needed to analyse and discuss topics relative to everyday life and basic survival. Purpose and coursebook content summary: to provide a high-level practice of language skills within international political contexts while at the same time providing proof of the level of English required to work in an international organization context or the ability to take up a course of study at the university level. The purpose of this coursebook is to explore some fundamental areas in English in immersive environments offering students the opportunity to develop and practice the crosscutting skills they need in their future careers. Learning Outcomes: • Confidently deal with different topics related to everyday life integrated into International Studies. • Satisfactory produce a university level essay on everyday life and basic survival. • Adequately follow and understand a wide range of spoken materials such as presentations and discussions. • Communicate effectively in face-to-face situations. • Applying knowledge and profound understanding. Skills and Competences: • Deal confidently with different types of everyday life topics and issues. • Write a proper academic level essay. • Follow and understand a range of spoken materials such as discussions, interviews and conversations. • Communicate effectively in face-to-face situations. “Bridge to Success: English for International Studies Students” develops this by encouraging students to explore, critically evaluate and appreciate a wide variety of authentic texts. The study of English involves exploring, responding to and composing texts: in and for a range of personal, social, historical, cultural and workplace contexts, using a variety of language modes, forms, features and structures. Meaningful use of English is achieved through responding and composing, which are typically interdependent and ongoing processes. “Bridge to Success: English for International Studies Students” provides a solid foundation for students who have a minimal understanding of the English Language. Students will very quickly overcome their fear of speaking and will soon improve their listening, reading, speaking and writing skills.
Keywords: English for Specific Purposes; International Studies; English Second Language; knowledge and profound understanding; listening, reading, speaking and writing skills